الإسناد عند علماء القراءات- مفهومه وأقسامه - جمعة أحمد همد آدم (AR-RĀ’IQ, 2023)
It is evidently known that the Holy Qur’an, and its various readings and narrations, have received great attention since its revelation till today. The `Isnäd “attribution” of the Noble Qur’an is among those aspects that have elicited great interest to the scholars. Hence, this study is carried out to reveal efforts of these scholar in the aspect of readings. The problem of the subject is supped up in the fact that the `Isnäd is considered to be one of the most important component of any acceptable reading; so it is one of the conditions in awarding a reading license, which is considered evidence of the person’s eligibility to take the lead in reading. This study attempts to answer the following questions: what are the efforts of the scholars of readings in taking care of the `Isnäd of the Qur’an? What are the types of readings? Are these evidences still continuing to our present time? The researcher followed the inductive and historical approach to answer these questions, in order to show the adoption of the `Isnäd in the frequent readings in different eras. The study revealed that these chains of narration were written in the books of readings, and in the licenses granted by the reciters to their students, and they still exist to our present era. The Quranic reading license is the process of audio transmission of the Holy Qur’an from one generation to the next, through oral reception, and it is valid to grant the `Isnäd and the license through modern means of communication and if the sheikh verifies the student’s mastery of reading, the visual face to face meeting with students and his Sheikh is not required for granting the license as such hearing is sufficient for the award of the licence.